Integrated regional development: Comparison of urban agglomeration policies in China. (March 2022) - Li, Lei; Ma, Shaojun; Zheng, Yilin; Xiao, Xinyue
Abstract: Rapid urbanisation has not only affected the division of urban administrative regions and economic development but also caused changes in land use patterns and urban-rural conflicts. Apart from being the main determinants of regional integration, urban agglomerations also represent a new form of spatial organisation to realise coordinated regional development. This study investigates China's national urban agglomeration development planning, which is guided by government decision-making and various plans aimed at sustainable land use. We use the TF-IDF algorithm, NVivo and statistical methods to analyse the keywords of urban agglomeration policies and the correlation between keywords. We also compare the positioning goals, focus areas and development paths of urban agglomeration policies. The main conclusions are as follows: (1) Urban agglomeration development planning mainly focuses on industrial construction, with additional emphasis on 'ecology', 'service', 'cooperation', 'innovation' and 'region' (2) On the basis of development and cooperation, urban agglomeration development planning puts forward research objectives and positioning suitable for development; (3) Urban agglomeration development should further develop modern agriculture, emergency systems, ecological construction and internal cooperation. This study's findings describe new ideas found by comparing urban agglomeration policies, which is helpful to understand the basis of formulating urban agglomeration development planning policies in China, and look forward to the long-term planning for the development of regional integration characteristics in China. Highlights: Local urban interaction focuses on the use of land space and sustainable development in the region. The analytical framework and method of comparative urban agglomeration development planning are put forward. The spatial layout and long-term planning of China's regional integration development is analysed comparatively. Modern agriculture, emergency systems, ecological construction and internal cooperation need urgent attention.